The Effectiveness of Think Pair Share Technique in Improving Students’ Reading Comprehension - Putri, Nur Auliah Anisa; Tahir, Muh.; Radhiyani, Fitri (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
The purpose of this study was to determine the effectiveness of the Think Pair Share (TPS) technique in improving students' reading comprehension. The population used in this study were the 11th-grade students of MAN Jeneponto. In this study, the researchers used a quasi-experimental design with a simple random sampling technique which was divided into two classes, there experimental class and the control class, each consisting of 33 students. The instrument used in this study was a reading test, which consisted of two parts, namely pre-test and post-test. The results showed that students in the experimental class were better compared to the control class. Seen from the mean score of the experimental class post-test was 88.61 while the mean score of the control class post-test was 74.30. Hypothesis testing in this study showed that the Sig. (2-tailed) of 0.000<0.05. It means the researchers concluded that the Think Pair Share (TPS) technique was effectively used in class XI.6 to improve students' reading comprehension.